IMPLEMENTASI PEMBELAJARAN MENGGUNAKAN MODUL BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Eka Sastrawati; Desri Guspita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article explains the effectiveness of ethnomathematics-based mathematics modules on students’ critical thinking skills. The research method used is a quantitative method with the type of post-test only control design with a cluster random sampling technique. Data were collected through documentation, observation, and test methods. The instrument used the validity test, the level of difficulty test, the test of discriminating power, and a reliability test. The data analysis technique used an analytical prerequisite and hypothesis tests (t-test). Based on the t-test result between the experimental and the control classes, it was obtained the value of 1.872 while ttable was 1.67. Above it, tcount > ttable, which means that the experimental class average is higher than the control class average. Hence, it can be concluded that the use of ethnomathematics-based mathematics modules on students’ critical thinking skills is better than learning that does not use ethnomathematics-based mathematics modules.